2019
DOI: 10.1111/nana.12506
|View full text |Cite
|
Sign up to set email alerts
|

The secessionist spectre: the influence of authoritarianism, nativism and populism on support for Quebec independence

Abstract: In recent years, Quebec has been undergoing a re‐evaluation of immigration and integration policies. The secessionist Parti Québécois had become the leader of this debate, which also coincided with a rise of right‐wing nativist, populist and sometimes authoritarian movements in other Western societies. This paper aims to evaluate the similarity or dissimilarity of Quebec's nationalism to these other nationalisms. We use the 2015 Canadian Election Study data to explore the influence of authoritarianism, nativis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Thus, the choice was made to exclude the BQ voters from the analysis. Because past research has found a relationship between those who hold populist attitudes and support of the BQ (Mayer et al, 2000), as well as a recent positive relationship with support for Quebec independence and voting for the independentist Parti Québécois (Blanchet and Medeiros, 2019), it is doubtful that populist attitudes would determine voting for the BQ differently.…”
Section: Data and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the choice was made to exclude the BQ voters from the analysis. Because past research has found a relationship between those who hold populist attitudes and support of the BQ (Mayer et al, 2000), as well as a recent positive relationship with support for Quebec independence and voting for the independentist Parti Québécois (Blanchet and Medeiros, 2019), it is doubtful that populist attitudes would determine voting for the BQ differently.…”
Section: Data and Resultsmentioning
confidence: 99%
“…Mudde (2007) defines such movements as a combination of nativist preferences for members of the native group; an authoritarian inclination for robust law and order policies; and populism, which he defines as a Manichean belief that opposes the pure people versus the corrupt elite and argues that politics should be an expression of the general will of the people. While nativism, authoritarianism and populism have been shown to form three distinct, orthogonal attitudinal dimensions (Blanchet and Medeiros, 2019;Rooduijn, 2014), the focus of the media and scholarly work on the nationalistic exclusionism of the populist radical right, often in the form of anti-immigrant and Islamophobic rhetoric, has led to nativism being incorrectly attributed as a core characteristic of populism (Rooduijn, 2019). Yet the surge of leftist populist parties, such as Syriza in Greece and Podemos in Spain, has forced scholars to explore vote choice for populist parties on a wider optic-a strand of electoral research into populist parties, rather than just populist radical right parties, that is still relatively nascent.…”
Section: A (Non-thin) Populist Ideologymentioning
confidence: 99%
See 1 more Smart Citation
“…Pioneering studies with regard to micro-level measures of populism have been published by Hawkins et al (2012) and Akkerman et al (2014), as well as Castanho Silva et al (2018) and Schulz et al (2018). Although the work presented in these studies advances our understanding of populist idea elements on the voter level, it rarely connects these idea elements with nativism, a combination necessary for painting the whole picture with regard to explaining electoral support for farright populist parties (notable exceptions using individual-level data on both populist and nativist attitudes are Blanchet and Medeiros (2019) , with their study of electoral support for the secessionist Parti Québécois, and Rooduijn (2014), with his analysis of Freedom Party voters). Hence, while the main focus of this contribution is on the east-west differences in AfD success, the simultaneous accounting of populist and nativist attitudes promises more direct answers to the more general question of the relative importance of these two factors for the right-wing populist vote than were previously available.…”
Section: Relevant Literature and Theoretical Foundationsmentioning
confidence: 98%
“…In Canada, the geographical focus of this dissertation, populism has been said to appear in the forms of increased desire for Western separation (Anderson & Coletto, 2019;Laycock, 2005), authoritarian legislation in provinces like Ontario and Quebec (Blanchet & Medeiros, 2019;Gerson, 2019), and as we will see in chapter seven, alarming amounts of anti-elitist, antiimmigrant and xenophobic organizations like ID Canada, Immigration Watch Canada, and "Yellow Vesters," among others. Canadians are more torn than ever on whether we let "too many immigrants" into the country, a trend that pollsters blame on "authoritarian populist movements" (EKOS, 2019).…”
Section: List Ofmentioning
confidence: 98%